2013
DOI: 10.5812/thrita.10301
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Voice Handicap Index and Specific Acoustic Measures in Patients With Muscle Tension Dysphonia

Abstract: Background: With regard to the multidimensional concept of the voice, different assessments are needed to diagnose and treat voice disorders. Additionally, it is important to know how various aspects of voice are compared and related to each other. Objectives: The purpose of this study was to examine the correlation between the Voice Handicap Index (VHI) score and the acoustic measures in different types of Muscle Tension Dysphonia (MTD). Patients and Methods: Eighteen females including 12 with primary MTD (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…47 Several researchers have indicated that the acoustic parameters of patients with MTD were significantly higher than those of people with normal voice conditions. 48 It would therefore be reasonable to assume that a number of the teachers in this study (those with higher NHR and ShdB) may have been unaware that they were suffering from the onset of MTD. These individuals would probably continue stressing their voices until vocal problems became severe.…”
Section: Discussionmentioning
confidence: 99%
“…47 Several researchers have indicated that the acoustic parameters of patients with MTD were significantly higher than those of people with normal voice conditions. 48 It would therefore be reasonable to assume that a number of the teachers in this study (those with higher NHR and ShdB) may have been unaware that they were suffering from the onset of MTD. These individuals would probably continue stressing their voices until vocal problems became severe.…”
Section: Discussionmentioning
confidence: 99%